Inversion Boundary Annihilation in GaAs Monolithically Grown on On‐Axis Silicon (001). Issue 22 (21st September 2020) - Li, Keshuang; Yang, Junjie; Lu, Ying; Tang, Mingchu; Jurczak, Pamela; Liu, Zizhuo; Yu, Xuezhe; Park, Jae‐Seong; Deng, Huiwen; Jia, Hui; Dang, Manyu; Sanchez, Ana M.; et al.
Abstract: Monolithic integration of III–V materials and devices on CMOS compatible on‐axis Si (001) substrates enables a route of low‐cost and high‐density Si‐based photonic integrated circuits. Inversion boundaries (IBs) are defects that arise from the interface between III–V materials and Si, which makes it almost impossible to produce high‐quality III–V devices on Si. In this paper, a novel technique to achieve IB‐free GaAs monolithically grown on on‐axis Si (001) substrates by realizing the alternating straight and meandering single atomic steps on Si surface has been demonstrated without the use of double Si atomic steps, which was previously believed to be the key for IB‐free III–V growth on Si. The periodic straight and meandering single atomic steps on Si surface are results of high‐temperature annealing of Si buffer layer. Furthermore, an electronically pumped quantum‐dot laser has been demonstrated on this IB‐free GaAs/Si platform with a maximum operating temperature of 120 °C. These results can be a major step towards monolithic integration of III–V materials and devices with the mature CMOS technology. Abstract : The monolithic integration of III–V materials on CMOS compatible Si (001) substrates for advanced applications on Si‐based photonic integrated circuits has attracted extensive interests for both academia and industry. This research focuses on a novel method to eliminate inversion boundary for the growth of GaAs buffer on on‐axis Si (001) substrates with single‐atomic‐height steps.